Pengembangan Modul Pembelajaran Teks Prosedur Berbantuan Komik Digital pada Siswa Kelas X di SMA Mamiyai Al-Ittihadiyah - Dalimunthe, Nafi Tri Amirah; Ali, Ali; Amaluddin, Amaluddin (Medan Resource Center, 2025)
This study aims to develop and evaluate the feasibility and effectiveness of a digital comic-assisted procedural text learning module for 10th-grade students at SMA Mamiyai Al-Ittihadiyah. Employing the Research and Development (R&D) approach using the 4D model—define, design, develop, and disseminate—the study systematically assessed the module's impact. The findings indicate that the developed module was rated as